Phytochemical, minerals and free radical scavenging profiles of Phoenix dactilyfera L. seed extract. Issue 1 (February 2016) - Adeosun, Abiola M.; Oni, Sarah O.; Ighodaro, Osasenaga M.; Durosinlorun, Okikiola H.; Oyedele, Omotayo M.
الملخص: أهداف البحث: يستخدم نوى تمر النخيل في الطب الشعبي لعلاج العديد من الأمراض. وقد تبين أن هذا النوى يساعد على خفض نسبة خطر الإصابة بالأمراض السرطانية، وبعض أمراض القلب والأوعية الدموية. وكذلك قد يساعد على تحسين مستوى الأداء الوظيفي وسلامة الجهاز المناعي للجسم. وعلى أساس مالدينا من معلومات تختص بتكوين النباتات وآثارها العلاجية أو الحيوية، سعت هذه الدراسة للبحث في الخصائص النباتية، ومكونات المعادن ومضادات الأكسدة لنوى تمر النخيل. طرق البحث: تم تقييم الخصائص النباتية والمكونات المعدنية فضلا عن قدرة نوى التمر على التأثير المضاد على الجذور الحرة باستخدام البروتوكولات القياسية. النتائج: وكانت محتويات القلويات، وفلافونيدات انثراكوينونيس، والصابونين، وتيربينويدس، والعفص (ملغ / ١٠٠جم من الوزن الجاف) ١٠٢.٢٧ موازي للأتروبين ٢٤٧، و ١.٢٣ موازي للكويرسيرتين٬ و٣٣٤.٩٣ موازي الإيزارين ١٩.٤٧، ١٢٤.٤١ و١٣٣.٢٠ على التوالي. أما محتوى الصوديوم، والبوتاسيوم، والكالسيوم، والمغنيسيوم، والحديد، والفوسفور، والزنك (ملغ / ١٠٠ جم من الوزن الجاف) فقد كان ٠.٦٧، ٧٨.١٢، ١٨.٢٠، ٠.٤٨، ٠.٨٢، ١٩.٣٢، و ٠.٢٥ على التوالي. أما التأثير المضاد للأكسدة للنوى ضد بعض الجذور الحرة فكان ١٠.٢١ ملغ / مل و ١.٦٧ ملغ / مل على التوالي. الاستنتاجات: خلصت هذه الدراسة إلى أن نوى تمر النخيل غني بالفلافونويد، وهي مجموعة من المواد المضادة للأكسدة مسؤولة على ما يبدو بشكل ملموس عن إلغاء الأضرار الجانبية للجذور الحرة على الجسم٬ وهذا يفسر التأثير العلاجي لنوى تمر النخيل في البحث. Abstract: Objectives: Phoenix dactilyfera L (date palm) seeds are used in traditional medicine for the treatment of several ailments. These seeds have been shown to lower the risk of cancer and some cardiovascular conditions as well as to improve the functionality and integrity of the immune system. On the basis of established associations between the composition of plants and their therapeutic or biological effects, this study sought to investigate the phytochemical, mineral, and antioxidant profiles of the date palm seed. Methods: The phytochemical and mineral compositions as well as the free radical scavenging capacity of the date palm seed were evaluated using standard protocols. Results: The alkaloids, flavonoids, anthraquinones, saponins, terpenoids, and tannins contents (mg/100 g dry weight) were 102.27 Atropine equivalents (ATE), 2471.23 Quercetin equivalents (QE), 334.93 Alizarin equivalents (ALE), 124.41, 19.47, and 133.20, respectively. The sodium, potassium, calcium, magnesium, iron, phosphorus, and zinc contents (mg/100 g dry weight) were 0.67, 78.12, 18.20, 0.48, 0.82, 19.32, and 0.25, respectively. The scavenging activities (EC50 ) of the seed against 1, 1-diphenyl-2-picryl hydrazyl (DPPH) and superoxide dismutase (SOD)-generated free radicals were 10.21 mg/mL and 1.67 mg/mL respectively. Conclusions: This study concluded that the date palm seed is rich in flavonoids, a group of polyphenolic antioxidants that are apparently responsible for the appreciable free radical scavenging effects. The polyphenolic compounds present in the investigated date seed may account for its therapeutic relevance in traditional medicines.